The Future of Automotive Personal Transport: Which Technologies - Electric, Service or the Combination Will Win In Different Markets? - Ge, Ping (2016)
This dissertation explores the future trends that are driving the transformation of the automotive industry. The author investigated the possibility of the key trends to get a framework of predictions of the automotive future. The main aspects of the research are the future potential of electric vehicles and shared mobility service in different markets, focusing on the U.S. and Chinese market, the two largest economies in the world. This dissertation aims to assess key trends on the future automotive personal transport and test its possibility. It contributes to providing insights for the industry players to position themselves in the new competitive structure.